Entropic estimation of rectification binary mixes at various variants of process computation. - A. K. Frolkova; L. A. Hahin (Тонкие химические технологии, 2008)
Optimization of power supply level of a two-unit rectification column on preproject stage of development unit of division indissolubly is connected to used process computation variant, which the certain set of explanatory variables answers. In clause production of entropy is considered as criterion of an optimal arrangement of power supply at rectification of binary mixes various nature. The analysis of entropy production is carried out at design and verifying variants.